Maxillofacial injuries resulting from the practice of sports activities: a cross-sectional study (Research, Society and Development, 2021)
The occurrence of maxillofacial injury increases as a result of a great demand for the practice of sports activities worldwide. Maxillofacial injuries can cause a series of losses for individuals who practice physical activities, resulting in emotional and functional consequences, decreased athletic performance, and financial losses. This study aimed to carry out an analysis of the data obtained from medical records of patients with maxillofacial injury due to sports practices. Medical records of patients seen at the Hospital between January 2008 and May 2019 were evaluated, whose attendance occurred as a result of sports activities. Independent variables were related to the type of maxillofacial injury that occurred. The records of 739 patients were analyzed. The occurrence of maxillofacial injury was more prevalent in adolescents and young adult males, as a result of playing soccer. The most prevalent type of injury was soft tissue, with the middle third of the face and the central region being the most frequently affected. Maxillofacial injury was more prevalent in adolescents and young male adults, due to the practice of soccer, typically affecting soft tissues, the middle third of the face, and the central region. The treatment performed was, mostly, conservative.